General anaesthesia-related complications of gut motility with a focus on cholinergic mechanisms, TRP channels and visceral pain - Zholos, Alexander V.; Dryn, Dariia O.; Melnyk, Mariia I. (Frontiers in Physiology, 2023)
General anesthesia produces multiple side effects. Notably, it temporarily impairs gastrointestinal (GI) motility following surgery and causes the so-called postoperative ileus (POI), a multifactorial and complex condition that develops secondary to neuromuscular failure and mainly affects the small intestine. There are currently limited medication options for POI, reflecting a lack of comprehensive understanding of the mechanisms involved in this complex condition. Notably, although acetylcholine is one of the major neurotransmitters initiating excitation-contraction coupling in the gut, cholinergic stimulation by prokinetic drugs is not very efficient in case of POI. Acetylcholine when released from excitatory motoneurones of the enteric nervous system binds to and activates M2 and M3 types of muscarinic receptors in smooth muscle myocytes. Downstream of these G protein-coupled receptors, muscarinic cation TRPC4 channels act as the major focal point of receptor-mediated signal integration, causing membrane depolarisation accompanied by action potential discharge and calcium influx via L-type Ca2+ channels for myocyte contraction. We have recently found that both inhalation (isoflurane) and intravenous (ketamine) anesthetics significantly inhibit this muscarinic cation current (termed mICAT) in ileal myocytes, even when G proteins are activated directly by intracellular GTPγS, i.e. bypassing muscarinic receptors. Here we aim to summarize ion channel and calcium signalling-related aspects of the cholinergic mechanisms in the gut, discuss exactly how these may be negatively impacted by general anaesthetics, while proposing the receptor-operated TRPC4 channel as a novel molecular target for the treatment of POI.